Kemampuan Self Compassion memprediksi Quarter Life Crisis pada Individu Dewasa Awal - Ayu Prabasari Dharmajayanti; I Rai Hardika; Agnes Utari Hanum Ayuningtias (MES Bogor, 2025)
This study aims to look at the role of self-compassion in predicting the occurrence of a quarter-century crisis in Early Adults. This research refers to the ability of self-compassion in helping individuals develop a willingness to rise and grow over the discomfort experienced. The sample of this study was 348 people obtained by the quota sampling technique, whose characteristics were Early Adult Individuals domiciled in Bali and aged 20-39 years. This study has two instruments: the self-compassion scale and the quarter-life crisis scale. All scales have proven reliable and valid based on the CFA test. Based on the results of a simple regression test, it was found that Self-compassion can predict the occurrence of a quarter-life crisis with a significance value of 0.00 and a percentage of 63.5%. The results of this study also illustrate that self-compassion and quarter-life crises grow significantly as a result of the internal motivation of the individual rather than the impulse from outside the individual self.